Proceso atención de enfermería en paciente adulto mayor con colelitiasis e hiperplasia prostática benigna. - Pachucho Andagana, Jefferson Stalyn (2022)
Cholelithiasis is defined as the presence of stones in the gallbladder, while prostatic hyperplasia is a condition that occurs more frequently in older adults. In cholelithiasis, the stones are usually asymptomatic, but may present with severe abdominal pain, nausea, emesis, and hyperthermia. While in benign prostatic hyperplasia we have frequency, nocturia and a feeling of emptying. The following case study is focused on an 87-year-old patient who refers to a clinical picture of ± 24 hours of evolution accompanied by severe abdominal pain of 8/10 on the VAS scale (pain scale) in the right hypochondrium that radiates to the back, nicturia, nausea, emesis and hyperthermia of 38ºC endig patient in a cholecystectomy. We proceed to the elaboration of the nursing care process in order to apply optimal care using the Nanda, Nic and Noc taxonomies, to identify the dysfunctional patterns that are compromising the patient's health status, and thus meet the proposed objectives. in this clinical case study.